(untitled) (Journal of Social Sciences Review, 2021)
The era of globalization is a complex phenomenon where individuals are faced with multiple challenges and responsibilities at the national, regional and global level. To fulfill responsibilities and turn challenges into opportunities, they need appropriate citizenship education that enables them to understand their rights and duties and act accordingly. Secondary education is a stage that determines the role of youth in the society through provision of citizenship education, therefore; the study focused on investigating the status of citizenship education in secondary schools of district Swat, Khyber Pakhtunkhwa. Study objectives were to; find out the current status of citizenship education at secondary level and to recommend strategies for betterment of citizenship education at secondary level. The study utilized quantitative descriptive survey research design. The population of the study was 1301 male secondary school teachers of District Swat. The researchers randomly selected a sample of 300 teachers for the collection of data. The researchers developed a questionnaire; validated in pilot study, further, reliability was ensured statistically. The data were collected with self-administered questionnaires and analyzed with means, standard deviation and chi-square test. The study found that secondary school teachers were unaware and were in a state of dissonance about the elements of citizenship education for secondary school curricula; however; there were materials in the curricula that supported citizenship education. The study recommended comprehensive citizenship education curricula, arrangement of professional development opportunities in citizenship for teachers and exposure of students to learn citizenship skills in secondary schools.